Evaluating the Bachelor of Education Program Based on the Context, Input, Process, and Product Model - Sankaran, Surendran; Saad, Norazlinda (Frontiers in Education, 2022)
The study aims to evaluate Bachelor of Education program based on CIPP model. The study is quantitative in nature and selected sample of 350 BEd students from University in Malaysia by applying non-proportionate stratified sampling and simple random sampling. The study used a survey questionnaire for data collection which was analyzed using Statistical Package of Social Sciences version 15.0. The findings indicated that lecturers and facilities, and the relevance and appropriateness of the program variables have significant relationship with the effectiveness of Bachelor of Education program The study concluded that it would be beneficial to the university in Malaysia in the long-term effort to improve the quality of the program offered and increase the performance and wisdom of the trainers.